2019
DOI: 10.1136/bmjopen-2018-027700
|View full text |Cite
|
Sign up to set email alerts
|

Here one year, gone the next? Investigating persistence of frequent emergency department attendance: a retrospective study in Australia

Abstract: ObjectivesPatients are presenting to emergency departments (EDs) with increasing complexity at rates beyond population growth and ageing. Intervention studies target patients with 12 months or less of frequent attendance. However, these interventions are not well targeted since most patients do not remain frequent attenders. This paper quantifies temporary and ongoing frequent attendance and contrasts risk factors for each group.DesignRetrospective population-based study using 10 years of longitudinal data.Set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…Alcohol and other drug use also correlate with frequent presentation. An Australian study examined over 8500 regular ED attenders finding that frequent attendance was associated with alcohol/drug abuse (OR 6.4, 99% CI 4.3–9.7) compared with a control group 5 . Almost 1 in 10 ED presentations have alcohol as a factor, 6 this can be up to one in eight in peak times, based on the Australasian College for Emergency Medicine's annual Alcohol Harm Snapshot Survey 7 .…”
Section: Different Presentation Typesmentioning
confidence: 99%
See 3 more Smart Citations
“…Alcohol and other drug use also correlate with frequent presentation. An Australian study examined over 8500 regular ED attenders finding that frequent attendance was associated with alcohol/drug abuse (OR 6.4, 99% CI 4.3–9.7) compared with a control group 5 . Almost 1 in 10 ED presentations have alcohol as a factor, 6 this can be up to one in eight in peak times, based on the Australasian College for Emergency Medicine's annual Alcohol Harm Snapshot Survey 7 .…”
Section: Different Presentation Typesmentioning
confidence: 99%
“…It is clear from the literature this is a heterogeneous group, albeit with some common characteristics. FA are more likely to be older than non‐frequent presenters, 5,10 with one study reporting a significant increase in presentations in the 70–79 years age group 2 . FA are more likely to be male, Aboriginal or Torres Strait Islander, be single 2,5 and often have complex social needs 1 .…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…High use of the emergency department (ED) is a ubiquitous phenomenon 14 but harbours a paradox: while high use is consistently found, the population of high-using patients is constantly changing. Studies in emergency medicine 15 16 have demonstrated that high use by an individual is a relatively unstable state: many high users in one time period become infrequent users in the next, and vice versa.…”
Section: Introductionmentioning
confidence: 99%